IRRIGATION SOLUTIONS IN CLINICAL ENDODONTICS: TYPES, PROPERTIES, AND ACTIVATION MECHANISMS - Sattarov, Islomjon (Medical science of Uzbekistan, 2025)
Relevance. Effective disinfection of root canals is one of the key factors for successful endodontic treatment. The complex anatomical structure of the canals, formation of necrotic tissue layers, and the presence of bacterial biofilms complicate complete cleaning and disinfection. Therefore, an in-depth study of irrigation solutions and their activation methods is highly relevant. By determining the properties, efficacy, and safety of irrigants such as sodium hypochlorite (NaOCl), EDTA, and others, it is possible to develop optimal clinical protocols. In particular, identifying the advantages of activation technologies such as passive ultrasonic irrigation (PUI) in biofilm removal is of great practical importance for dental practitioners. Materials and methods of the study. The literature review is based on an analysis of scientific articles published between 2000 and 2024. Articles were searched using the PubMed, Scopus, and Web of Science databases. The search keywords included “endodontic irrigation,” “root canal disinfection,” “irrigant activation,” and “sodium hypochlorite endodontics.” A total of 86 articles were initially identified, of which 48 were deemed relevant to the topic. The selection criteria included the chemical composition and efficacy of irrigation solutions, comparative analysis of irrigation protocols, and mechanisms of irrigant activation. The main focus was on analyzing the physicochemical properties and activation methods (ultrasonic, sonic, laser-assisted) of NaOCl, EDTA, CHX, MTAD, and QMix irrigants. Research results. Sodium hypochlorite (NaOCl) was recognized as the “gold standard” irrigant due to its broad-spectrum antimicrobial and tissue-dissolving properties. A 17% EDTA solution effectively removed the necrotic layer. A 2% chlorhexidine solution provided prolonged antimicrobial effects but lacked tissue-dissolving capabilities. Modern solutions such as MTAD and QMix demonstrated multifunctionality and promising results. Meta-analyses showed that the combination of NaOCl and EDTA with ultrasonic activation yielded the most effective outcomes. The recommended optimal clinical protocol included initial irrigation with NaOCl, intermediate rinse with 17% EDTA, and final rinse with NaOCl; ultrasonic activation was applied at all stages. Conclusion. Irrigation plays a crucial role in ensuring the success of endodontic treatment. NaOCl remains the primary irrigant due to its antimicrobial and tissue-dissolving properties, while EDTA is an effective adjunct for removing necrotic and bacterial layers. Activation methods, especially ultrasonic irrigation, enhance the efficacy of irrigants and demonstrate superiority in biofilm removal. Optimal protocols combine NaOCl and EDTA with ultrasonic activation to ensure maximum disinfection and minimal risk.